Optimization Of Shariah-Based Digital Marketing Strategy To Increase Smartfren Brand Loyalty Through Customer Engagement According To Islamic Economic Concept - Martha Laila Arisandra; Nanda Nanta Kusuma (Universitas Islam Darul 'ulum Lamongan, 2026)
This study aims to optimize sharia-based digital marketing strategies to enhance Smartfren's brand loyalty through customer engagement according to the concept of Islamic economics. The background of this research is the low optimization of sharia principles in the digital marketing practices of telecommunication operators in Indonesia, particularly in the aspects of moderation (al-wasathiyyah) and justice (al-haq wa al-adl), as well as the gap between high attitudinal loyalty and the company's financial performance. This study employs a quantitative method with a survey approach. Data were collected through online questionnaires distributed to 200 Smartfren customers in the Greater Jakarta area, interviews with 30 customers at Smartfren outlets, observation of @smartfrenworld social media activities over three months, and documentation from company reports and official publications. Data analysis was conducted using descriptive and inferential statistics with Pearson correlation. The theoretical frameworks include Islamic Marketing Theory (Kartajaya & Sula, 2006), Customer Engagement Theory (Brodie et al., 2011), Brand Loyalty Theory (Oliver, 1999), and Maqashid Sharia Theory (Asy-Syatibi). The results show that the optimization level of Smartfren's sharia-based digital marketing is moderate (mean 3.51 out of 5), with the highest indicator being the absence of content violating religious values (3.96) and the lowest indicators being the frequency of promotional notifications that disturb comfort (3.15) and excessive advertising claims (3.28). The level of customer engagement is also moderate (3.29), with the affection dimension being relatively good but the activation dimension (commenting and sharing content) being low. Meanwhile, Smartfren's brand loyalty level is high (3.75), particularly in conative loyalty, ie, the intention to remain subscribed (3.95). There are significant positive correlations between sharia digital marketing and brand loyalty (r=0.512, p<0.01), between customer engagement and brand loyalty (r=0.568, p<0.01), and between sharia digital marketing and customer engagement (r=0.482, p<0.01). These findings confirm that customer engagement serves as a mediating variable connecting the optimization of sharia-based digital marketing with Smartfren's brand loyalty. This study concludes that optimizing sharia-based digital marketing strategies can enhance Smartfren's brand loyalty; However, improvements are needed in moderating notification frequency, honest promotional claims, information transparency, and increasing responsiveness to customer interactions on social media. The logical consequence of this research for the development of Islamic education theory and practice is that sharia values such as honesty, justice, moderation, and transparency are not only relevant in business contexts but must also be integrated into the curriculum, learning methods, and governance of Islamic educational institutions. Islamic education should produce graduates who not only understand these values normatively but can also apply them practically in various aspects of life, including digital marketing and organizational management.